Evidence against Zika virus infection of pets and peri-domestic animals in Latin America and Africa. (25th January 2022) - Oliveira-Filho, Edmilson F. de; Carneiro, Ianei O.; Fischer, Carlo; Kühne, Arne; Postigo-Hidalgo, Ignacio; Ribas, Jorge R. L.; Schumann, Peggy; Nowak, Kathrin; Gogarten, Jan F.; de Lamballerie, Xavier; Dantas-Torres, Filipe; Netto, Eduardo Martins; et al.
Abstract : Decades after its discovery in East Africa, Zika virus (ZIKV) emerged in Brazil in 2013 and infected millions of people during intense urban transmission. Whether vertebrates other than humans are involved in ZIKV transmission cycles remained unclear. Here, we investigate the role of different animals as ZIKV reservoirs by testing 1723 sera of pets, peri-domestic animals and African non-human primates (NHP) sampled during 2013–2018 in Brazil and 2006–2016 in Côte d'Ivoire. Exhaustive neutralization testing substantiated co-circulation of multiple flaviviruses and failed to confirm ZIKV infection in pets or peri-domestic animals in Côte d'Ivoire ( n =259) and Brazil ( n =1416). In contrast, ZIKV seroprevalence was 22.2% (2/9, 95% CI, 2.8–60.1) in West African chimpanzees ( Pan troglodytes verus ) and 11.1% (1/9, 95% CI, 0.3–48.3) in king colobus ( Colobus polycomos ). Our results indicate that while NHP may represent ZIKV reservoirs in Africa, pets or peri-domestic animals likely do not play a role in ZIKV transmission cycles.